2001
DOI: 10.1007/s00381-001-0519-2
|View full text |Cite
|
Sign up to set email alerts
|

Posthemorrhagic hydrocephalus in preterm infants: long-term follow-up and shunt-related complications

Abstract: The neurological outcome was not related to the necessity for or to complications of a shunt. Programmable valve systems and neuroendoscopy appear to be helpful in the overall management and in the treatment of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 30 publications
1
52
0
6
Order By: Relevance
“…The studies involving children with a diagnosis of hydrocephalus are mostly series of retrospective case and they consider different etiologies as a unique group [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The studies involving children with a diagnosis of hydrocephalus are mostly series of retrospective case and they consider different etiologies as a unique group [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The authors also reported that survival differences in infants occurred within the first few months after surgery, which is consistent with our results and those of other studies in which a failure rate of 48%-58% within the first year is described. 8,14,23,36,42,45 This is also emphasized by Reinprecht et al, 41 who reported results from a cohort of 42 preterm infants with posthemorrhagic hydrocephalus and shunt implantation. They noted occlusion of the distal catheter as the primary cause for revision, which occurred mainly during the first few months.…”
Section: Discussionmentioning
confidence: 65%
“…They have not prescribed any therapy during 42 days for protection of white matter. But in massive IVH a very rapid clinical changes are possible and also the rapid development of hydrocephalus, and in these situations an early VPS is recommended (19,20,36,41,55). Levi and colleagues had 83% obstruction of shunt in preterm infants with PHH(in 83% of cases).…”
Section: Resultsmentioning
confidence: 99%